High expression of nectin-1 indicates a poor prognosis and promotes metastasis in hepatocellular carcinoma - Wang, Xuequan; Xing, Ziming; Chen, Huazhong; Yang, Haihua; Wang, Qiupeng; Xing, Tongjing (Frontiers in Oncology, 2022)
Objectives: Nectins are a new class of cell adhesion molecules that play an important role in tumorigenesis and disease progression. The aim of this study was to investigate prognostic and pathogenetic roles of nectins in hepatocellular carcinoma (HCC). Methods: The expression levels of the nectin family in HCC and their role in prognosis were analyzed by bioinformatics analysis based on the TCGA-LIHC database. The correlations between nectins and immune cells were analyzed by Timer. Functional enrichment of the Nectin1 coexpression network was evaluated in the TCGA cohort. The expression levels of nectin-1 were detected by immunohistochemistry and western blot. A transwell kit was used for cell migration experiment. Cell proliferation was analyzed by the Cell Counting Kit-8. Results: The expression levels of nectin-1 protein in cancer tissues of 28 patients with HCC were higher than those in paracancerous tissues. KM plotter analysis showed that the high expression of all nectin family numbers was related to the poor prognosis of HCC patients. The abnormal expression of nectin-1 effectively distinguished the prognosis at different stages and grades of HCC. The high expression of 17 methylation sites of nectin-1 gene was related to the high overall survival(OS) of HCC patients. KEGG analysis of genes negatively correlated with nectin-1 showed that they were closely related to the regulation of immune effector process. Pearson correlation analysis showed that nectin-1 was significantly positively correlated with multiple immune genes and immune cells infiltration. Cell proliferation of the knockdown (KD) group decreased significantly compared with the NC-KD group. The number of metastatic cells in the KD group decreased significantly compared with that in the NC-KD group. Conclusions: Abnormal expression of nectins and multiple methylation sites closely correlate with the poor prognosis in HCC patients. Nectins are related to immune cell infiltration and immune-related genes. In particular, nectin-1 can promote the proliferation and migration of liver cancer cells and distinguish the prognosis at different stages and grades of HCC. Nectin-1 might be a new potential molecular marker for the prognostic evaluation and also a therapeutic target for HCC.